Inhalation Anesthetics for Postoperative Nausea and Vomiting in General Anesthesia Patients - Saifuddin, Ircham; ., Destiana; Aziz, Muhammad Abdul; Palestin, Bondan (Asian Journal of Pharmaceutical Research and Development, 2023)
Background: Postoperative nausea and vomiting is an anesthetic complication which is related to various factors. Patients who experience postoperative nausea and vomiting have worse quality of recovery which causes delay in patient discharge from the hospital which will increase the cost of care. Objective: To knowing the effect of inhalation anesthetics on postoperative nausea and vomiting in general anesthesia patients at Dr Soedirman Hospital Kebumen. Method: The study is a quasi-experimental quantitative study with a pre-test-post-test design with a control group design. The population of the study were all patients undergoing general anesthesia at Dr Soedirman Hospital Kebumen. The study was conducted in September - October 2022 with a sample of 56 respondents for each group which was determined using a purposive sampling technique. Data analysis using the Wilcoxon test. Result: Results of analysis of the effect of inhalational anesthesia on postoperative nausea and vomiting in general anesthesia patients at Dr Soedirman Hospital Kebumenp (sig) 0.000. Conclusion: There is an effect of inhalation anesthetics on postoperative nausea and vomiting in general anesthesia patients